(untitled) (Bangladesh Journal of Zoology, 2025)
One hundred fresh specimens of pama croaker Otolithoides pama Hamilton, 1822 (Perciformes: Sciaenidae) from Vatiary costal area, Chittagong, Bangladesh, were necropsied to explore the species composition, study the community structure, microhabitat preference and infection dynamics of helminth parasites. Overall, 79.0% of examined fishes were parasitized by twelve species of parasites namely, Microcotyle spinicirrus and Pseudempleurosoma haywardi (Monogenea), Uterovesiculurus hamati, Phyllodistomum folium, Helicometrina elongata and Stephanostomum sp. (Digenea), Parachristianella trygonis (larva) and Unidentified cestode larva (Cestoda), Philometra protonibeae, Spirocamallanus notopteri and larvae of Contracaecum sp. (Nematoda) and Acanthocephalus sp. (Acanthocephala). The present parasite community was dominated by nematodes, Contracaecum sp. was the core species with highest prevalence (67%) and abundance (8.82). Except the unidentified cestode larva (rare species), the rests were satellite species. Among the recovered parasites, M. spinicirrus (gill), P. protonibeae (ovary) and Acanthocephalus sp. (intestine) showed strict organ specificity and Contracaecum sp. was cosmopolitan in nature found to harbor body cavity, stomach, intestine and pyloric caeca. The females (84.91%) were found to be more susceptible to parasitic infection than male (72.34%). Stages of sexual maturity of fish had a significant influence on the prevalence, the gravid fishes were found to be 100% infected and the infection rate was lowest in the spent fishes. Significant positive correlation was observed between weight and prevalence. The association between infection site (organs) and prevalence was also significant. The intestine was the most preferred microhabitat (55.0%) while the liver, kidney, testis and swim bladder were resistant to parasitic infection. Bangladesh J. Zool. 53(1): 79-98, 2025